A novel device for automated determination of the smoke point with non-invasive adaptation of ASTM D1322 normalized lamps. (25th August 2020) - Corral-Gomez, Lis; Rodriguez-Rosa, David; Juarez-Perez, Sergio; Martín-Parra, Andrea; Rubio Gomez, Guillermo; Moya-Fernandez, Francisco
Abstract: Particulate matter emission from the combustion of fossil fuels is a major concern due to its harmful effects on human health and impact on engine performance. Measurement of the smoke point of these fuels is a key issue in order to assess the tendency of fuels to generate particulate matter. Although certain commercial devices for measuring the smoke point are available, they are very expensive and their precision can still be improved. This paper proposes a novel low-cost device to achieve precise and repetitive smoke point measurements. It is based in an improved image processing algorithm that reduces the measurement error compared to previously developed methods. The device design allows easy adaptation to the smoke point lamp normalized in the American Society for Testing and Materials (ASTM) D1322, without any modification to the lamp.